Pentingnya Belajar Bahasa Inggris di Era Globalisasi Bagi Anak-Anak di Panti Asuhan Al-Jami’yatul Washliyah - Liza Afilia Suryani; Husni Thamrin (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Education in general is a life process in developing each individual to be able to live and carry on life, so that the individual becomes an educated person. Language is a means of communication or a means connecting or communicating between one another, between members of society, between one country and another which consists of individuals expressing thoughts, feelings, desires that are in each individual. With increasing age, every child experiences language and concept development quickly, especially if it is supported by the introduction of aspects (English) from an early age so that it is useful for them when they grow up competition with global world. The purpose of this study is to introduce English and apply the importance of English in the era of globalization at the Al-Jami’yatul Washliyah orphanage. The intervention program carried out through several stages in general, namely Engagement, Intake and Contract, Assessment, Planning, Intervention, Evaluation and Termination. The end result is that children can get to know the basics of English more.